2016
DOI: 10.3136/fstr.22.145
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Bread Making Properties by the Addition of Alginates

Abstract: (1996) studied the influence of alginate on starch retrogradation by analyzing the possible interactions between hydrocolloids and starch or gluten. Rosell et al. (2001b) showed that the addition of sodium alginate improved wheat dough stability during proofing.The reasons why alginates are effective in bread making are currently unknown; thus, in order to expand seaweed usage in the future, it is necessary to determine the mechanism by which alginates function in bread making. In this study, bread making test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Therefore, PGA improved bread quality with respect to specific volume and porosity (Table 3). Another possible reason is that some researchers found that the expansion of bread dough increased as a result of the addition of PGA to wheat flour and that the CO 2 gas produced by the yeast could be efficiently trapped by the PGA wheat flour bread dough [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, PGA improved bread quality with respect to specific volume and porosity (Table 3). Another possible reason is that some researchers found that the expansion of bread dough increased as a result of the addition of PGA to wheat flour and that the CO 2 gas produced by the yeast could be efficiently trapped by the PGA wheat flour bread dough [16].…”
Section: Discussionmentioning
confidence: 99%
“…They found that PGA increased loaf specific volume, with concentrations of 3.0% PGA and 2.0% PGA having the largest effect as well as a significant impact on the springiness of bread. Tabara et al [16] investigated the impact of six different alginic acid-related materials on the quality of bread, specifically height (mm) and specific volume (cm 3 /g). They found that compared to the control sample, 2.0% (w/w) PGA significantly increased the height and specific volume of bread, indicating a positive impact of PGA addition on the quality of bread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to improve the quality of starch-based food through the improvement of the processing technology. Studies have shown that when sodium alginate is added to wheat flour for bread making, it can increase the baking rate of bread, as well as the swelling of bread dough [ 4 ]. It was found that extracellular polysaccharides produced by lactic acid bacteria (LAB) during fermentation improved the quality of bread more than the addition of extracellular polysaccharides alone [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been claimed that XG can alter the qualities of bread, such as increasing hardness and lengthening the rising time (Kondakci et al, 2015). SA is found in brown algae and is widely used in the food industry (Lee et al, 2008; Tabara et al, 2016). Salehi, 2019 reports that SA shows yellow layer cake hardening retardation and quality improvement.…”
Section: Introductionmentioning
confidence: 99%